Evaluation of Physical, Mechanical, and Wear Properties of Jatropha Shell Powder Reinforced Epoxy Glass Fiber Composites - Lalta Prasad; Rahul Bairwan; Anshul Yadav; Anil Kumar; Virendra Kumar; Jerzy Winczek (Journal of Natural Fibers, 2022)
Jatropha residue (shells and de-oiled cake) is a waste product from the oil processing industries and is toxic. Jatropha shell powder (JSP) was used as filler to fabricate an epoxy glass fiber hybrid composite material. The effect of different wt.% (10, 15 and 20%) and Jatropha shell powder sizes (150, 150–250, and 250–300 µm) on physical-mechanical characteristics of hybrid composites were studied. It was discovered that the tensile strength of the hybrid composite (79.6 MPa) improved significantly with 15 wt % JSP loading of size 150–250 µm as compared to epoxy glass fiber composite (35.7 MPa). The hybrid composite specific wear rate (0.079 mm3/Nm) reduced significantly (89%) as compared to the glass fiber composite material. The impact strength of the hybrid composite material is increased by 4 times of simple composite. The SEM images revealed that the fibers pull out from the lamina due to a lack of interfacial bonding between glass fiber, epoxy, and JSP. Additionally, the TOPSIS method was used to predict the best hybrid composite material using the experimental results. It can be concluded that JSP powder can be used for epoxy glass fiber composite, which would reduce environmental pollution by increasing the green building resource base.